Understanding traditional healers' role in the HIV cascade of care: a qualitative study among stakeholders in Mwanza, Tanzania - Richie Hong, BSc; Dunstan Matungwa, PhD; Jeremiah Kidola, MD; Daniel Pungu, BSc; Matthew Ponticiello, BSc; Robert Peck, MD; Radhika Sundararajan, MD (The Lancet Global Health, 2022)
Background: HIV is endemic in Tanzania (prevalence 5%). However, less than half of Tanzanians are aware of their HIV status and only 75% of Tanzanian adults living with HIV are on antiretroviral therapies (ART). Informal health-care providers, such as traditional healers, frequently serve as the first line of health-care services in Tanzania. To understand gaps in HIV care, we conducted a qualitative study to understand how traditional healers interface with adults living with HIV along the cascade of care. Methods: This study was conducted in Mwanza, Tanzania between November, 2019, and May, 2020. We invited traditional healers (n=15), clients of traditional healers (n=15), biomedical health-care facility staff (n=15), and adults living with HIV (n=15) to participate in a single qualitative interview. Two community focus groups were also conducted among male participants (n=8) and female participants (n=8). All participants were aged 18 years or older. Interviews explored individual experiences with traditional healers and biomedical health-care facilities, and perceptions of traditional healers with respect to HIV care. Interviews were conducted in Kiswahili by Tanzanian research assistants, transcribed, and later translated into English for analysis. By means of a content-analysis approach, transcripts were independently reviewed by two authors (RH, RS) to develop a coding scheme. Coded data were grouped into a framework that characterised the ways through which traditional healers engage with adults living with HIV throughout the HIV treatment cascade. This study was approved by pertinent ethical review boards. Participants provided written informed consent. Findings: 60 interviews and two focus groups were conducted and analysed. Qualitative data showed that adults living with HIV frequently engaged with traditional healers throughout the HIV cascade of care, from the pre-diagnosis to the post-diagnosis stages. Traditional healers were noted, in some cases, to directly facilitate HIV testing, whereas others were described as delaying testing through continued traditional treatment. Adults living with HIV commonly used traditional medications concurrently with ARTs. There was concern that traditional healers contributed to ART non-adherence because some adults living with HIV used traditional therapies in search of a purported HIV cure. Our findings suggest that traditional healers interact with adults living with HIV throughout the HIV cascade of care and that collaboration between traditional healers and biomedical health-care facilities could improve HIV outcomes. Interpretation: Qualitative data show that traditional healers can both support and impede patient's engagement with HIV services. Our findings show that traditional healers consistently interact with adults living with HIV in both the pre-diagnosis and post-diagnosis contexts, and they should be integrated into existing health-care infrastructure to improve engagement with HIV testing and treatment. Funding: Weill Cornell Kellen Junior Faculty Fellowship Award.